Acupuncture, chiropractic and osteopathy use in Australia: a national population survey - Polus Barbara; Myers Ray; Lin Vivian; Zhang Anthony L; Xue Charlie CL; Story David F (BMC, 2008)
Abstract Background There have been no published national studies on the use in Australia of the manipulative therapies, acupuncture, chiropractic or osteopathy, or on matters including the purposes for which these therapies are used, treatment outcomes and the socio-demographic characteristics of users. Methods This study on the three manipulative therapies was a component of a broader investigation on the use of complementary and alternative therapies. For this we conducted a cross-sectional, population survey on a representative sample of 1,067 adults from the six states and two territories of Australia in 2005 by computer-assisted telephone interviews. The sample was recruited by random digit dialling. Results Over a 12-month period, approximately one in four adult Australians used either acupuncture (9.2%), chiropractic (16.1%) or osteopathy (4.6%) at least once. It is estimated that, adult Australians made 32.3 million visits to acupuncturists, chiropractors and osteopaths, incurring personal expenditure estimated to be A$1.58 billion in total. The most common conditions treated were back pain and related problems and over 90% of the users of each therapy considered their treatment to be very or somewhat helpful. Adverse events are reported. Nearly one fifth of users were referred to manipulative therapy practitioners by medical practitioners. Conclusion There is substantial use of manipulative therapies by adult Australians, especially for back-related problems. Treatments incur considerable personal expenditure. In general, patient experience is positive. Referral by medical practitioners is a major determinant of use of these manipulative therapies.